Case report: Clinically mild encephalitis/encephalopathy with a reversible splenial lesion: an autopsy case - Hayashi, Maho; Ueda, Midori; Hayashi, Koji; Kawahara, Ei; Azuma, Shin-ichiro; Suzuki, Asuka; Nakaya, Yuka; Asano, Rei; Sato, Mamiko; Miura, Toyoaki; Hayashi, Hiromi; Hayashi, Kouji; et al. (Frontiers in Neurology, 2024)
Clinically mild encephalitis/encephalopathy with a reversible splenial lesion is a clinicoradiological syndrome characterized by transient neuropsychiatric symptoms and hyperintensity of the splenium of the corpus callosum on diffusion-weighted MRI. Although intramyelin edema and inflammatory cell infiltration can be predicted by MRI, the pathology of the splenium of the corpus callosum remains unknown.We encountered a case of clinically mild encephalitis/encephalopathy with a reversible splenial lesion and hypoglycemia in a patient who died of sepsis, and an autopsy was performed.The postmortem pathological findings included intramyelin edema, myelin pallor, loss of fibrous astrocytes, microglial reactions, and minimal lymphocytic infiltration in the parenchyma.Based on these findings, transient demyelination following cytotoxic edema in the splenium of corpus callosum was strongly considered as a pathogenesis of "clinically mild encephalitis/encephalopathy with a reversible splenial lesion" associated with hypoglycemia, and it could be generalized for the disease associated with the other causes. As cytotoxic edema could be the central pathology of the disease, the recently proposed term, cytotoxic lesions of the corpus callosum may be applicable to this syndrome.